Colonials in conflict : Europeans in British and German East Africa and the First World War - Steinbach, Daniel (Trinity College (Dublin, Ireland). Department of History, 2014)
This thesis analyses the experience of conflict in the colonies of British and German East Africa in the context of the First World War. In particular, the focus of this research is on the, to date under-examined, perspectives of the Europeans who inhabited, and fought for their nation in, these colonial territories. To explore the varied European perspectives on the war as it unfolded, the thesis draws on four case studies that represent the most dynamic fields of research within current First World War studies: the outbreak of hostilities, the internment of enemy aliens, the experience of war from the soldiers’ perspective, and the occupation of conquered territory.
Embargo End Date: 2022-01-01
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin, 2014